International Folk Music Council (International Library of African Music, 1958)
The Honorary Secretary of the Society attended the Tenth Meeting of the General Assembly of the International Folk Music Council in Liege, Belgium, from July 28th to August 2nd, 1958. A great deal of interesting matter was discussed although most of the attention of the Council was, naturally, directed towards the many Folk Musics of Europe. There were, however, several Members present whose interests were primarily African.
Keywords: African Music